Measuring and analyzing the impact of public spending on the inflation rate in Iraq for the period (2020-2023) using the threshold regression model (Entrepreneurship Journal for Finance and Business, 2025)
Public spending is one of the most important tools used by governments to achieve their economic and social goals, studying the relationship between public spending and inflation in Iraq is one of the important and vital topics, especially in light of the challenges facing the Iraqi economy such as oil price fluctuations and thus fluctuations in financial revenues, and the correct public spending management through which inflation rates can be monitored and controlled.The research aimed to measure and analyze the impact of public spending on inflation in Iraq through the use of modern standard methods where the threshold model was used (Threshold Regression), as the research found that there are four thresholds during the research period, in the first threshold the relationship was positive between public spending and the inflation rate when the inflation rate is less than (3.699%), and that the increase in public spending by one unit It will lead to an increase in the inflation rate by (0.040%) before reaching this threshold, but in the value of the second threshold of inflation and after exceeding the rate of (3.699%), it is less than (4.399%) and that increasing  public spending by one unit will also lead to an increase in the inflation rate by (0.216%) before reaching this threshold, while the third threshold for the inflation rate after exceeding the rate of (4.399%), which is less than (6.399%) and that Increasing public spending by one unit will lead to an increase in the inflation rate by (40.26%) before reaching this threshold, while the fourth and last threshold for an inflation rate is greater than or equal to (6.399%), and that increasing public spending by one unit will lead to an increase in the inflation rate by (0.419%) before reaching this threshold. The research concluded with a number of proposals, the most prominent of which is the need for decision-makers to follow up the levels of public spending carefully at low spending levels. There may not be a significant impact on inflation in the future, and monitoring spending at high levels, there may be a significant impact that requires arbitrary policies to prevent hyperinflation.